Pola Pembentukan Konstruksi Verba Serial dalam Bahasa Batak Toba (Teori X-Bar) - Saragih, Elza Leyli Lisnora; Mulyadi, Mulyadi (GERAM: Gerakan Aktif Menulis, 2020)
This study aimed to describe the construction and how the formation pattern of serial verbs in Batak Toba language through X-bar theory. A qualitative descriptive method with data collection techniques using note-taking and interview techniques was used. Data were collected from interviews with native speakers and the text of Toba Batak language almanac. In analyzing the data, a method of distribution was employed. The results showed that the formation pattern of serial verbs in the Batak Toba language consisted of 4 types namely which were [transitive V1+ transitive V2], [transitive V1+intransitive V2], [intransitive V1+ transitive V2], and [intransitive V1 + intransitive V2]. The first type, [transitive V1+ transitive V2] is formed from the predicate that followed by the object + the predicate and followed by the object. The next formation, [V1 transitive + V2 intransitive] is formed from predicates followed by object + predicates and not followed by the object. The later type, [V1 intransitive + V2 transitive] is formed from predicates that not followed by object + predicates and followed by an object. Further, the last type, [intransitive V1 + V2] is formed from a predicate not followed by an object + a predicate and not followed by an object.